Impacto das políticas de distanciamento social e os desafios para sua implementação durante a pandemia de COVID-19 no estado do Ceará, nordeste do Brasil - Almeida, Camylla Nathallia (2024)
Infectious and contagious diseases have historically represented a threat to living beings, this study focuses on this topic taking as a backdrop the period of the Covid-19 Pandemic. Therefore, we present as Objective: Analyze the impact of social distancing policies and the challenges for their implementation during the Covid-19 pandemic in the state of Ceará. Method: Cross-sectional study carried out between January and March 2022, through an online survey available via Google Forms, and disseminated via email and social networks (Facebook, LinkedIn, Instagram and Whatsapp). The questionnaire covered socio-demographic data, issues related to Covid-19 and periods of lockdown, including perceptions of sanitary and public health measures developed in Ceará during the first, second and third waves of the disease, in the years 2020, 2021 and 2022, respectively. Participants were recruited through convenience sampling, using the snowball technique, including adults over 18 years of age, residents of the state during the pandemic and who experienced periods of lockdown. Results: 1,079 participants were captured, the majority of whom were female (64%), aged between 30-40 years old (37%), mixed-race (55%), married/in a stable union (49.1%), studying post-graduate studies. degree (44%), income up to 3 minimum wages (50.2%) and mostly residents of the capital (72%). 84.1% of individuals highlighted the importance of using masks for the entire population and 89.5% reported that social isolation is an effective measure to control the spread of Covid-19. Regarding the experience during the first wave (April to May/2020) and second wave (March to May/2021), the population pointed out that it was a stressful/distressing period (79.10%) and (66.20%) respectively, different from the perception experienced in the third wave (December/2021 to January/2022), where they reported it being a calm/normal phase (46.80%). Around 79% of those interviewed reported that they obtained sufficient information from the state government about ways to prevent the disease and 58% think that the government is moderately prepared to face future epidemics. Regarding the news about Covid-19 broadcast by the media (radio and TV), 55.2% responded that they were true/real, however the information disseminated via the internet/WhatsApp was considered alarmist/exaggerated (39.3%). Furthermore, more than 80% reported that the health and economic sectors were those that suffered the greatest impacts during the pandemic. Conclusion: The study showed that during periods of confinement during the Covid-19 pandemic, the majority of the population adhered to the public health measures passed on by the government of the state of Ceará, but that there may have been failures in communication due to the dissemination of news false reports through social media, increasing feelings of anguish during lockdown. The results in question may be useful for future mitigation strategies.